#### Answer

$3$

#### Work Step by Step

Substitute $x=-1$ into $f(x)$ to get: $f(-1)=\sqrt{3(-1)+12}=\sqrt9=3$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$3$

Substitute $x=-1$ into $f(x)$ to get: $f(-1)=\sqrt{3(-1)+12}=\sqrt9=3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.